Advanced sensing and control for connected and automated vehicles - Huang, Chao; Du, Haiping; Zhao, Wanzhong; Zhao, Yifan; Yan, Fuwu; Lv, Chen (MDPI, 2022)
In recent years, connected and automated vehicles (CAV) have been a transformative technology that is expected to reduce emissions and change and improve the safety and efficiency of the mobilities [...]